Development of parameters for an industry-specific methodology for calculating the electric energy storage system for gas industry facilities - Ivan S. Tokarev (Записки Горного института)
The issue of determining the main parameters of electric energy storage systems – power and energy intensity – is being considered, the determination of which is a fundamentally important task when introducing such devices into the power supply systems of enterprises for both technical (technological) and economic reasons. The work analyzes problems that can be solved by installing electricity storage systems at gas industry facilities. An industry-wide methodology has been developed for calculating the parameters of an electricity storage system based on traditional methods and methods aimed at minimizing the standardized cost of electricity with adaptation to the conditions of the gas industry. A distinctive feature of the presented methodology is the ability to determine the power and energy intensity of electricity storage systems when performing several functions. The methodology was tested at a typical gas industry facility – the Yarynskaya compressor station of OOO Gazprom Transgaz Ukhta, a characteristic feature of which is an autonomous power supply system. An example is given of calculating the electricity storage normalized cost using an improved LCOS indicator, which takes into account the effect of changing the fill factor of the electrical load schedule on the amount of gas consumption by a power plant for its own needs. To confirm the economic efficiency of introducing electricity storage systems calculated using the above methodology, calculations of the integral effect, net present value and efficiency index are presented.